2023
DOI: 10.1038/s41598-022-25970-0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-glutamyl transferase and risk of all-cause and disease-specific mortality: a nationwide cohort study

Abstract: Population-based data regarding the prognostic implication of gamma-glutamyl transferase (GGT) have been inconsistent. We examined the association of GGT with all-cause and disease-specific mortality. Using the Korean nationwide database, we included 9,687,066 subjects without viral hepatitis or cirrhosis who underwent a health examination in 2009. Subjects were classified into three groups by sex-specific tertile of serum GGT levels. The underlying causes of death were classified by 10th Revision of the Inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…32 The association between serum GGT activity and mortality from liver disease or cancer has been investigated in the general population. 13,14 Kazemi-Shirazi et al showed that serum GGT concentrations above the reference level were significantly associated with cancer-, hepatobiliary disease-, and vascular disease-related mortality in both men and women. 31 In contrast, studies investigating the association between serum GGT levels and mortality from various diseases in patients with T2DM are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The association between serum GGT activity and mortality from liver disease or cancer has been investigated in the general population. 13,14 Kazemi-Shirazi et al showed that serum GGT concentrations above the reference level were significantly associated with cancer-, hepatobiliary disease-, and vascular disease-related mortality in both men and women. 31 In contrast, studies investigating the association between serum GGT levels and mortality from various diseases in patients with T2DM are limited.…”
Section: Discussionmentioning
confidence: 99%
“…5 GGT has been regarded as a surrogate for oxidative stress and has been shown to play a role in the pathogenesis of various diseases, including CVD, cancer, and lung disease. [6][7][8] In addition to its clinical utility as an indicator of hepatobiliary diseases and alcohol consumption, GGT has also been reported to be correlated with cardiometabolic risk factors, such as visceral adiposity, hepatic triglyceride accumulation, metabolic syndrome, and T2DM, [9][10][11] and to be associated with a high risk of all-cause and CVDspecific mortality in both the general population [12][13][14] and patients with T2DM. [15][16][17] Nonetheless, except for CVDspecific mortality, there exists a paucity of data regarding whether GGT is associated with disease-specific mortality in patients with T2DM, as compared with those without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Sample size was determined using the G*power program (ver. 3.1.9.2; University of Kiel, Kiel, Germany), and with reference to the main effect size (d) of 1.11 reported by Kim et al [ 23 ], significance level (α) of 0.05, and power (1-β) of 0.8, the sample size was calculated to be 14 for each group. To account for a 15% dropout rate, we aimed to recruit at least 17 participants for each group.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Korean older women have a higher rate of dementia than male senior citizens [ 22 ], and pulmonary function decline occurs more frequently due to thoracic kyphosis [ 23 ]. In addition, although the rate of depression and falls is significantly higher, older women have a longer lifespan, so more research on maintaining a healthy life for the older women is needed [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased GGT levels can predict an individual's risk of cardiovascular disease (CVD), regardless of alcohol consumption (3). Previous studies have shown that a higher level of serum GGT, even within the normal range, is associated with all-cause mortality, cardiovascular mortality, and cancer-related mortality (4).…”
Section: Introductionmentioning
confidence: 98%